The influence of occupational stress and job satisfaction on burnout among healthcare workers in the UAE: A cross-sectional study - Yousef Aljawarneh; Ahmad Al-Bashaireh; Zainab Albikawi; Osama Alkouri; Nour Ali Alrida; Mohammad Abuadas; Alanoud Alobaidly; Mahrah Alyileili; Shayma Alyileili; Wadha Alyileili; Fatmah Alhefetti; Amna Alhefeiti; et al. (PLoS ONE, 2025)
Background Healthcare Workers (HCWs) frequently face high levels of occupational stress, job dissatisfaction, and burnout due to the demanding nature of their work. In the United Arab Emirates (UAE), these challenges are further intensified by the rapid growth of the healthcare sector and increasing workloads, making it particularly critical to study these variables. Therefore, this study aimed to investigate the influence of occupational stress and job satisfaction on burnout and to identify the key predictors of burnout among HCWs in the UAE. Methods A cross-sectional study was conducted among 498 HCWs from hospitals and primary healthcare centers under Emirates Health Services/ Ministry of Health and Prevention. Data was collected using the Work Stress Questionnaire (WSQ), Maslach Burnout Inventory (MBI), and Minnesota Satisfaction Questionnaire (MSQ). Results The mean level of occupational stress was moderate, with a mean of 34.68 (SD = 10.15). The most affected subscales were “work-to-leisure time interference” and “influence at work.” The level of job satisfaction was also moderate, with a mean of 3.13 (SD = 0.75), and the highest satisfaction was related to extrinsic factors. The levels of burnout were notably high for emotional exhaustion and depersonalization, whereas “personal accomplishment” was less affected. Stepwise multiple regression analysis revealed significant predictors of emotional exhaustion (R 2 = 0.530), including individual demands, work-to-leisure conflict, job satisfaction, income, and marital status. Depersonalization was predicted by indistinct organization, income, and employment type (R 2 = 0.254). The least affected personal accomplishment subscale was predicted by occupational stress, age, education, nationality, and working hours, accounting for 6.9% of the variance (R 2 = 0.069). Conclusion The present study has highlighted the urgent need for targeted interventions to reduce occupational stress and improve job satisfaction to combat burnout among HCWs in the UAE. Organizational strategies should focus on workload management, promoting a healthy work-life balance, and clearly defining roles. These findings offer a foundation for informed policy actions to safeguard HCW well-being and elevate healthcare quality.